The dual action of poly(ADP-ribose) polymerase -1 (PARP-1) inhibition in HIV-1 infection: HIV-1 LTR inhibition and diminution in Rho GTPase activity - Rom, Slava; Reichenbach, Nancy L.; Dykstra, Holly; Persidsky, Yuri (Frontiers in Microbiology, 2015)
The transcription of HIV-1 (HIV) is regulated by complex mechanisms involving various cellular factors and virus-encoded transactivators. Poly(ADP-ribose) polymerase 1 (PARP-1) inhibition has emerged recently as a potent anti-inflammatory tool, since PARP-1 is involved in the regulation of some genes through its interaction with various transcription factors. We propose a novel approach to diminish HIV replication via PARP-1 inhibition using human primary monocyte-derived macrophages (MDM) as an in vitro model system. PARP-1 inhibitors were able to reduce HIV replication in MDM by 60-80% after 7 days infection. Long Terminal Repeat (LTR) acts as a switch in virus replication and can be triggered by several agents such as: Tat, tumor necrosis factor α (TNFα), and phorbol 12-myristate 13-acetate (PMA). Overexpression of Tat in MDM transfected with an LTR reporter plasmid led to a 4.2-fold increase in LTR activation; PARP inhibition resulted in 70% reduction of LTR activity. LTR activity, which increased 3-fold after PMA or TNFα treatment, was reduced by PARP inhibition (by 85-95%). MDM treated with PARP inhibitors showed 90% reduction in NFκB activity (known to mediate PMA- and TNFα-induced HIV LTR activation). Cytoskeleton rearrangements are important in effective HIV-1 infection. PARP inactivation reduced actin cytoskeleton rearrangements by affecting Rho GTPase machinery. These findings suggest that HIV replication in MDM could be suppressed by PARP inhibition via NFκB suppression, diminution of LTR activation and its effects on the cytoskeleton. PARP appears to be essential for HIV replication and its inhibition may provide a potent approach to treatment of HIV infection.